Self-Assembly of Symmetrical and Asymmetrical Alkyl Esters in the Neat State and in Oleogels - Avendaño-Vásquez, Gilda; De la Peña-Gil, Anaid; Charó-Alvarado, Maria E.; Charó-Alonso, Miriam A.; Toro-Vazquez, Jorge F. (Frontiers in Sustainable Food Systems, 2020)
Saturated alkyl esters play an important role in determining the functional properties of the vegetable waxes used in the formulations of natural cosmetics and edible oleogels. We studied the relationship between the thermo-mechanical properties and crystal microstructure developed by saturated symmetrical (SE: 14:14, 16:16, 18:18, 20:20, and 22:22) and asymmetrical (AE: 18:14, 18:16, 18:20, 18:22) esters in the neat state and in oleogels. Additionally, we evaluated the effect of 1-stearoyl-glycerol (MSG; 0.5 and 1%) in the development of SE and AE oleogels. The X-ray and microscopy analysis in the neat state showed that SE self-assembled developing plate-like crystals, while AE developed acicular-like crystals. Microscopy analysis indicated that AE and SE followed similar crystallization behavior in the oleogels. The AE oleogels had higher elasticity (G′) than the SE oleogels. In both types of oleogels as the ester carbon number increased the oleogels' G′ decreased and crystal size increased. The addition of just 0.5% MSG, particularly in the AE oleogels, limited the decrease in G′ as the ester carbon number increased, mainly because MSG decreased crystal size. The calorimetry results suggested that during cooling the MSG and the alkyl esters developed a co-crystal. Nevertheless, part of the MSG did not interact with the ester molecules and crystallized independently. These MSG crystals acted as active fillers of the microstructure formed by the co-crystals. The overall effect was that in comparison with the alkyl ester oleogels the alkyl ester oleogels with 0.5 and 1% MSG had higher G′ with frequency independent rheological behavior. This rheological behavior was particularly evident with the AE oleogels. Therefore, ester composition and molecular structure (i.e., symmetry or asymmetry) greatly influence its molecular self-assembly and subsequently the oleogels' thermo-mechanical properties. Studies using molecular mechanics modeling are underway to establish the mechanism for AE and SE self-assembly with and without MSG. The overall goal is to understand and control the crystallization of vegetable waxes for the development of functional edible oleogels.